Professionalism of Female Teachers in Managing the Dual Role between Family and Work at Madrasah Tsanawiyah Khatibul Umam Kurma, Polewali Mandar Regency - Salma; Sitti Jamilah Amin; Marhani; Amiruddin; Ahdar (Universitas Muhammadiyah Palu, 2025)
This thesis discusses the Professionalism of MTs Khatibul Umam Kurma Female Teachers in Carrying Out Dual Roles in Polewali Mandar Regency. This study aims to find out the description of female teachers at MTs Khatibul Umam Kurma, Polewali Mandar Regency and the professionalism of female teachers who carry out dual roles at MTs Khatibul Umam Kurma, Polewali Mandar Regency. This research is a field research using qualitative methods. Researchers go directly to the field through observations, in-depth interviews, and documentation. The data sources are school principals and female teachers at MTs Khatibul Umam Kurma, Polewali Mandar Regency. Furthermore, the data analysis used is the Milles and Huberman analysis technique. Meanwhile, the data validity testing technique used is triangulation. The results of the study show that (1) female teachers at MTs Khatibul Umam Kurma, Polewali Mandar Regency face the challenge of dual roles as educators and family members. A teacher must manage time effectively to balance teaching duties and domestic responsibilities. (2) The professionalism of female teachers is not only measured by academic competence and character, but also by emotional and social intelligence that allows them to remain innovative and adaptive. Communication skills, cooperative skills, problem solving, time management, and the application of a professional code of ethics are the main keys in carrying out these roles. Support from husbands, family, and colleagues is helpful in reducing pressure and strengthening the professionalism of female teachers.